Nanosecond time-resolved characterization of a pentacene-based room-temperature MASER - Salvadori,E; Breeze,JD; Tan,K-J; Sathian,J; Richards,B; Fung,MW; Wolfowicz,G; Oxborrow,M; Alford,NM; Kay,CWM (Scientific Reports, 2017)
The performance of a room temperature, zero-field MASER operating at 1.45 GHz has been examined. Nanosecond laser pulses, which are essentially instantaneous on the timescale of the spin dynamics, allow the visible-to-microwave conversion efficiency and temporal response of the MASER to be measured as a function of excitation energy. It is observed that the timing and amplitude of the MASER output pulse are correlated with the laser excitation energy: at higher laser energy, the microwave pulses have larger amplitude and appear after shorter delay than those recorded at lower laser energy. Seeding experiments demonstrate that the output variation may be stabilized by an external source and establish the minimum seeding power required. The dynamics of the MASER emission may be modeled by a pair of first order, non-linear differential equations, derived from the Lotka-Volterra model (Predator-Prey), where by the microwave mode of the resonator is the predator and the spin polarization in the triplet state of pentacene is the prey. Simulations allowed the Einstein coefficient of stimulated emission, the spin-lattice relaxation and the number of triplets contributing to the MASER emission to be estimated. These are essential parameters for the rational improvement of a MASER based on a spin-polarized triplet molecule.